10. BLOOD PRESSURE ON ADMISSION CHARACTERISTIC OF MULTIVESSEL DISEASE PATIENT IN ST-SEGMENTS ELEVATION MYOCARDIAL INFARCTION UNDERGOING PRIMARY PERCUTANEOUS INTERVENTION. (May 2021) - Harlyjoy, Beta Canina; Kuncoro, Ario Soeryo; Soenarta, Arieska Ann; Sukmawan, Renan
Abstract : Background: In ST-segment elevation myocardial infarction (STEMI), several factors have been identified to be related with adverse outcome after PCI, including number of vessels involved, left ventricular function, and low TIMI flow. Blood pressure during admission is associated with risk of cardiovascular event. Component of blood pressure in STEMI patients may be correlated with in-hospital event. Objective: This study aimed to observe blood pressure characteristic of STEMI patients according to number of infarcted vessels at National Cardiovascular Center Harapan Kita (NCCHK). Methods: We collected medical record data of STEMI patients undergoing primary PCI in NCCHK from January to December 2020. Results: This study included 344 patients. Multivessel disease, defined as significant stenosis in 3 2 major coronary arteries, occurred in 220 patients (64.0%). In the single vessel patients, LAD lesions occurred in 86 patients (69.4%), LCx in 9 patients (7.3%) and RCA in 29 patients (23.4%). Compared to single vessel patients, multivessel disease patients had lower blood pressure, with systolic blood pressure of 125.98 ± 25.77 vs 127.72 ± 23.11 ( p  = 0.522), diastolic blood pressure (DBP) of 74: 28–128 vs 79: 47–123 ( p  = 0.006) and mean arterial pressure of 91.67: 47–147 vs 95.17: 58–142 ( p  = 0.052). Chi-Square test showed that DBP < 70 mmHg is associated with multivessel disease, odds ratio of 1.75 with 95% CI of 1.10–2.79 ( p  = 0.018). In the single-vessel patients, there were statistically significant difference of DBP according to the culprit lesions. Patients with LAD lesion tend to have higher DBP (81: 51–120 vs 75.5: 47–123, p  = 0.021) while RCA lesion tend to have lower DBP (74: 47–123 vs 81: 51–120, p  = 0.029) Conclusion: Lower diastolic blood pressure is associated with multivessel disease in STEMI patients undergoing PCI.